Horizontal mergers, cost savings, and network effects. (9th March 2022) - Cosnita‐Langlais, Andreea; Rasch, Alexander
Abstract: We consider a horizontally differentiated oligopoly and investigate the relationship between merger cost savings and network effects for the incentives of firms to merge and for the postmerger welfare outcomes. We show that it is more profitable to be an insider rather than an outsider of the merger, unless both cost savings and network effects are too low. Mergers can improve customer and total welfare provided both cost savings and network effects are high enough. We find that the possibility for network effects to lead to a Pareto improvement through merger is shown to depend on the number of outside firms.